Nutrient adequacy, patient acceptability and cost of the Philippine General Hospital regular diet. - Sta. Ana, Maria T. P.
The Philippine General Hospital (PGH) is a government hospital concerned with health service for the community's indigent while at the sane time providing health education and training to medical and paramedical students, trainees and staff. This study was done to determine the nutrient adequacy, patient acceptability and cost of the regular diet served at PGH, to find out whether this segment of the community that depends on PGH for health care and training id being provided at diet that is adequate, acceptable and within reasonable costs. It is 1 measure of the quality of existing dietary services. Previously no such in-depth study of a hospital diet has been done and it is hoped that with this study as a start, similar projects will be undertaken to ensure the maintenance of quality in the food served to hospital patients and staff. The study covered a total period of 28 days so that a standard serving portion of each diet meal served during this period was weighed, computed for nutrient content and each total day's meals evaluated for nutrient adequacy. After every meal, 25 of adult patients on regular diet were interviewed for meal acceptability with rating levels following the 9-point hedonic scale. Meal costs were determined in 2 ways: total expense divided by total number of meals served and a per recipe per meal cost determination. Dietary evaluation showed mean adequacy for most of the nutrients studied except for ascorbic acid for all age groups and iron for female in the 25-29 and 30-49 age groups. Qualitatively the diet came out with ideal proportions for carbohydrate, protein and fat at respectively 56, 15 and 29 in the male diet and 51, 15.5 and 33.5 in the female diet. In the male diet, 60.9 of protein was animal derived while protein in the female diet was 66 animal. Of the different food groups, found inadequate were the "Vitamin C-rich fruits", "kamote or potatoes", "leafy and yellow vegetables" and the "beans and nuts" groups for all age groupings of both sexes. For the 25-year age group also found inadequate were "cereals", "sugar" and "fat". Acceptability rating levels of 7.12 in the male and 7.15 in the female respondents coincided with the "like moderately" level of the 9-point hedonic scale. Found most acceptable was lunch and least acceptable was supper for the female and breakfast for the male respondents. A mere 1 of the respondents found the meals not acceptable.